Revealing research preferences in conservation science. Issue 3 (22nd May 2021) - Montana, Jasper; Sandbrook, Chris; Robertson, Ellen; Ryan, Melanie
Abstract: Conservation researchers are increasingly drawing on a wide range of philosophies, methods and values to examine conservation problems. Here we adopt methods from social psychology to develop a questionnaire with the dual purpose of illuminating diversity within conservation research communities and providing a tool for use in cross-disciplinary dialogue workshops. The questionnaire probes the preferences that different researchers have with regards to conservation science. It elicits insight into their motivations for carrying out research, the scales at which they tackle problems, the subjects they focus on, their beliefs about the connections between nature and society, their sense of reality as absolute or socially constituted, and their propensity for collaboration. Testing the questionnaire with a group of 204 conservation scientists at a student conference on conservation science, we illustrate the latent and multidimensional diversity in the research preferences held by conservation scientists. We suggest that creating opportunities to further explore these differences and similarities using facilitated dialogue could enrich the mutual understanding of the diverse research community in the conservation field.